Perilaku agresif dan penanganannya melalui konseling islami - Zain Irwanto (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
The purpose of this study were (1) To determine the factors causing the emergence of Aggressive Behavior student at SMPN 1 Tondong Tallasa Pangkep district. (2) To know the description of the results of the counseling process Islami against the aggressive behavior of students at SMPN 1 Tondong Tallasa Pangkep district. This study used a qualitative approach to the type of case studies with data collection through interviews, observation, and documentation. The results showed that (1) the factors agtresif behavior was arrogant, selfish, family economy, family environment, (2) the application of Islamic counseling to the students' problems aggressive behavior indicate a change student behavior from aggressive to not be aggressive.